Social Skins of the Head : Body Beliefs and Ritual in Ancient Mesoamerica and the Andes - Tiesler, Vera; Lozada, María Cecilia (Book collections on Project MUSE., 2018)
"The meanings of ritualized head treatments among ancient Mesoamerican and Andean peoples is the subject of this book, the first overarching coverage of an important subject. Heads are sources of power that protect, impersonate, emulate sacred forces, distinguish, or acquire identity within the native world. The essays in this book examine these themes in a wide array of indigenous head treatments, including facial cosmetics and hair arrangements, permanent cranial vault and facial modifications, dental decorations, posthumous head processing, and head hunting. They offer new insights into native understandings of beauty, power, age, gender, and ethnicity. The contributors are experts from such diverse fields as skeletal biology, archaeology, aesthetics, forensics, taphonomy, and art history."--